Holocene pool formation in oligotrophic fens from boreal Québec in northeastern Canada. (March 2018) - Garneau, Michelle; Tremblay, Louis; Magnan, Gabriel
At the biogeographical limit between the boreal and the subarctic domain in northeastern Canada, peatlands are mainly oligotrophic fens characterized by a dominance of aquatic microforms such as pools and wet hollows. These peatlands present similar features as the appa mires in Scandinavia. They show evidence for recent water-table rise indicated by tree mortality, physical degradation of strings, and pool expansion. This study aims to evaluate the timing of pool inception and their impact on the long-term dynamics of these microforms within two patterned oligotrophic fens in the Laforge region, northern Québec. Plant macrofossil and testate amoeba analyses from sediment underneath pools were used along with radiocarbon dating to reconstruct peatland pool dynamics over the Holocene. Our data indicate that wet hollows or shallow pools developed at minimal ages between 4200 and 2500 cal. a BP. Pool initiation in the peatlands of the Laforge region corresponds to the climate shift toward cooler and wetter conditions from the onset of the late-Holocene cooling. We suggest that the pool developed as secondary features influenced by short growing seasons, low accumulation rates, and wet conditions, which in turn affected the wettest microforms to shift into permanent pools. The differential response of microforms to shift in surface wetness shows the complexity of processes involved in pool initiation.